Stent Design Affects Femoropopliteal Artery Deformation. Issue 1 (July 2019) - MacTaggart, Jason; Poulson, William; Seas, Andreas; Deegan, Paul; Lomneth, Carol; Desyatova, Anastasia; Maleckis, Kaspars; Kamenskiy, Alexey
Abstract : Background: Poor durability of femoropopliteal artery (FPA) stenting is multifactorial, and severe FPA deformations occurring with limb flexion are likely involved. Different stent designs result in dissimilar stent–artery interactions, but the degree of these effects in the FPA is insufficiently understood. Objectives: To determine how different stent designs affect limb flexion-induced FPA deformations. Methods: Retrievable markers were deployed into n = 28 FPAs of lightly embalmed human cadavers. Bodies were perfused and CT images were acquired with limbs in the standing, walking, sitting, and gardening postures. Image analysis allowed measurement of baseline FPA foreshortening, bending, and twisting associated with each posture. Markers were retrieved and 7 different stents were deployed across the adductor hiatus in the same limbs. Markers were then redeployed in the stented FPAs, and limbs were reimaged. Baseline and stented FPA deformations were compared to determine the influence of each stent design. Results: Proximal to the stent, Innova, Supera, and SmartFlex exacerbated foreshortening, SmartFlex exacerbated twisting, and SmartControl restricted bending of the FPA. Within the stent, all devices except Viabahn restricted foreshortening; Supera, SmartControl, and AbsolutePro restricted twisting; SmartFlex and Innova exacerbated twisting; and Supera and Viabahn restricted bending. Distal to the stents, all devices except AbsolutePro and Innova exacerbated foreshortening, and Viabahn, Supera, Zilver, and SmartControl exacerbated twisting. All stents except Supera were pinched in flexed limb postures. Conclusions: Peripheral self-expanding stents significantly affect limb flexion-induced FPA deformations, but in different ways. Although certain designs seem to accommodate some deformation modes, no device was able to match all FPA deformations.